OPTIMALISASI PENGELOLAAN EKOWISATA HUTAN MANGROVE "LATI TUO" UNTUK MENINGKATKAN PEREKONOMIAN WARGA DESA KLEMPANG SARI - Bulan, Dewi Embong; Bestziel, Jheardy; Toufik, Julianti Fitria; Septiana, Yessi; Ashari, Devisa Febrilia; Oktavianingsih, Okky; Savitri, Ratna; Fazar, Reza Nur; Apriyana, Faidah; Khumairoh, Ai Syarifah; S, Riski Alfira Wulandari; Margareta, Fira Santi; Ibrahim, Ibrahim (Jurnal Abdi Insani, 2023)
Tourism, including environmental tourism, has become one of Indonesia's second-greatest foreign exchange contributors after petroleum and natural gas. The potential for Mangrove tourism is growing due to the ecotourism philosophy, which stresses nature conservation and local communities, particularly coastal areas. The solution to the issue of developing tourism activities in conservation areas is ecotourism. There is a Mangrove Forest ecotourism area called "Lati Tuo" in Klempang Sari Village, Kuaro District, Paser Regency, however, its management is not yet optimal. This activity intends to improve the management of "Lati Tuo" Mangrove ecotourism by developing supporting infrastructure at ecotourism sites. All activities involved teams from the village, Mulawarman University students, ecotourism managers, and the community around the location. The actions carried out include preparation, problem identification, planning, implementation, and assessment. Activities carried out at the "Lati Tuo" mangrove ecotourism site, Klempang Sari Village. This time, ecotourism management optimization operations are more focused on building several supporting facilities for visitor comfort, because tourist comfort is one of the variables that might influence tourists' decisions to visit a tourist site. Making chairs at each corner of the bridge and creating warning signs are among the activities that have taken place. Aside from that, there was the creation of gazebo name boards, the creation of Latin name plates for plants in the mangrove forest "Lati Tuo," and the creation of "Lati Tuo" Love Padlocks. The development of supporting facilities at the "Lati Tuo" mangrove ecotourism site was completed smoothly. The support of all stakeholders, including the village officials, ecotourism management, and the Klempang Sari Village Community, is critical to the success of this activity.